Existence and uniqueness of a Lotka–Volterra reaction–diffusion model with advection term. (December 2018) - Tang, De; Ma, Li
Abstract: In this paper, we investigate a reaction–diffusion two-competition species model with advection term under the Dirichlet boundary condition. By employing implicit function theorem, the principal spectral theory and other important formulas, we obtain the existence and uniqueness of spatial nonhomogeneous solutions under some given parameters conditions.